Are frailty markers associated with serious thoracic and spinal injuries among motor vehicle crash occupants?. Issue 1 (July 2016) - Oskutis, Morgan Q.; Lauerman, Margaret H.; Kufera, Joseph A.; Shanmuganathan, Kathirkamanathan; Burch, Cynthia; Kerns, Timothy; Ho, Shiu; Scalea, Thomas M.; Stein, Deborah M.
Abstract : BACKGROUND: While age is a known risk factor in trauma, markers of frailty are growing in their use in the critically ill. Frailty markers may reflect underlying strength and function more than chronologic age, as many modern elderly patients are quite active. However, the optimal markers of frailty are unknown. METHODS: A retrospective review of The Crash Injury Research and Engineering Network (CIREN) database was performed over an 11-year period. Computed tomographic images were analyzed for multiple frailty markers, including sarcopenia determined by psoas muscle area, osteopenia determined by Hounsfield units (HU) of lumbar vertebrae, and vascular disease determined by aortic calcification. RESULTS: Overall, 202 patients were included in the review, with a mean age of 58.5 years. Median Injury Severity Score was 17. Sarcopenia was associated with severe thoracic injury (62.9% vs. 42.5%; p = 0.03). In multivariable analysis controlling for crash severity, sarcopenia remained associated with severe thoracic injury ( p = 0.007) and osteopenia was associated with severe spine injury ( p = 0.05). While age was not significant in either multivariable analysis, the association of sarcopenia and osteopenia with development of serious injury was more common with older age. CONCLUSIONS: Multiple markers of frailty were associated with severe injury. Frailty may more reflect underlying physiology and injury severity than age, although age is associated with frailty. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level IV.